(untitled) (Journal of Open Law, Technology & Society, 2013)
In Turkey, whether distinguishing software as Free Open Source Software (FOSS) or Proprietary Close Source Software (PCSS), there is no precise ‘National ICT Policy in Public Institutions’. It is crucial to evaluate ICT Policy, particularly how and why it is incomprehensive, as a case study, to conceptualise ICT Policy from a national psyche. The study focuses on the reasons for not ‘governing’ ICT Policy and identifies the conditions behind this omission. I argue how FOSS is deliberately ignored due to; obvious, institutional inertia, path dependence and ungovernable ICT changes and arguably, corruption in new public management. The study concludes that Turkey has failed to produce written ICT Policies and to establish pervasive and trustworthy (flexible) ICT ecosystems, which recognise either a balanced development between FOSS & PCSS or a FOSS favourable system. Turkey has taken a de-facto ICT Policy, by which Microsoft dominant markets control public institutions. Whilst techno-institutional lock-ins politically exist and are irreversible, the future is mistakenly defined as a Procrustean ICT Bed Strategy. Globally, ICT Policy is understood to be an ‘experimental strategy’ (not definitive), perhaps for the purpose of ongoing negotiations and positioning of a national state within global networks because of evident nationally prioritised values and interests. The dynamic and failing nature of ICT ecosystems leads to ‘no broken promise’.